Where did the river go? Testing the hypothesis of rivers discharging into the Gulf of Sirt (East Mediterranean) during the late Pleistocene - Barbara Mauz; Esam Abdulsamad; Saleh Emhanna; Noureddine Elmejdoub; Moez Mansoura; Michael Rogerson (PLoS ONE, 2025)
Large quantities of freshwater supplied by rivers are, amongst other factors, required to slow down deep-water ventilation and allow sapropels to form. Spatial distribution of sapropels in the East Mediterranean as well as its thermohaline circulation point to rivers reaching the African coast to the west of the Nile. Here we study the coastal plain of the Gulf of Sirt (Libya) to find evidence for rivers. Using field survey, laboratory analyses on coastal samples and published geological data from wells and surface mapping we find a carbonate-rich, clastic-starved Gulf coast prevailing during MIS 5 and early MIS 4. The coastal plain is a flat and featureless Pliocene surface lacking evidence for a large-scale allogenic river but showing some water discharge in a desert depression situated ca 200 km inland. While we have to conclude that no river reached the Gulf of Sirt during MIS 5, we found evidence for ponding of brackish water in the Chott El Jerid (Tunisia) and support the idea of a Irharhar – Chott water pathway.